2020
DOI: 10.7150/jca.37282
|View full text |Cite
|
Sign up to set email alerts
|

Epstein Barr Virus Associated Lymphomas and Epithelia Cancers in Humans

Abstract: Epstein Barr virus (EBV) is a cosmopolitan oncogenic virus, infecting about 90% of the world's population and it is associated to tumors originating from both epithelia and hematopoietic cells. Transmission of the virus is mainly through oral secretions; however, transmission through organ transplantation and blood transfusion has been reported. In order to evade immune recognition, EBV establishes latent infection in B lymphocytes where it expresses limited sets of proteins called EBV transcription programs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
105
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 169 publications
(191 reference statements)
0
105
0
2
Order By: Relevance
“…This in turn leads to transcriptional activation of viral LMP genes (LMP-1 and -2) promoting cellular proliferation [ 45 , 46 , 47 ]. During latency 0, no EBNA protein is expressed, while only one EBNA (EBNA1) is expressed during latency I and II, and during latency III, all six EBNAs are expressed [ 48 , 49 , 50 ]. Further, the co-presence of both EBNA1 and LMP1 in our cohort can be explained by the fact that in EBV-infected cells, in the latent phase, EBNA1 and LMP1 are expressed in a cancer-specific manner [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This in turn leads to transcriptional activation of viral LMP genes (LMP-1 and -2) promoting cellular proliferation [ 45 , 46 , 47 ]. During latency 0, no EBNA protein is expressed, while only one EBNA (EBNA1) is expressed during latency I and II, and during latency III, all six EBNAs are expressed [ 48 , 49 , 50 ]. Further, the co-presence of both EBNA1 and LMP1 in our cohort can be explained by the fact that in EBV-infected cells, in the latent phase, EBNA1 and LMP1 are expressed in a cancer-specific manner [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up study will associate virulent factors with the EBV genotypes, and possibly suggest a mechanistic role of the factors in disease etiology, which will ultimately drive the search for therapeutic targets. The classification of EBV into the two main geographically distinct genotypes, 1 and 2, is based on sequence polymorphism in EBNA-2, -3A, -3B and -3C [ 21 , 22 ]. However, since EBNA-2 has the least percentage of sequence homology EBV typing has been done using this protein [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…E6 can associate with Bac-Bax and other pro-apoptotic proteins [118]. The onco-protein E6 can magnify cell proliferation without interference of E7 by means of its C-terminal PDZligand domain [119], as well as mediate suprabasal cell proliferation [120] which may lead to disruption of cell to cell adhesion and progression of carcinoma. Studies showed that the downregulation of E-cadherin increases the risk of metastasis in HNSCC [121].…”
Section: Human Papilloma Virus and Emtmentioning
confidence: 99%